Reservatório de usinas hidreletricas, recursos hídricos e conflitos socioambientais: o exemplo da usina hidrelétrica de Balbina - Santos, Thiago Flores dos (2011)
The water is a valuable environmental possessions, but before the existence of several standards and concepts that aim at the maintenance of the essential characteristics of the hydric resources, the existent scenery in many reservoirs of hydroelectric stations in Brazil is of deterioration of the quality of the water with increase of socioenviromental conflicts made a list to the use of the hydric resources. This environmental problematic is caused by the lethargy of the Public Power which does not practice actions of management of the environment, which contributes to the environmental imbalance in reservoirs, with the consequent deterioration of the quality of the water. On the other side, are not included in the final cost of the hydroelectric undertakings all the costs socioenviromental resultants of the activity of generation of energy through the use of the hydric resources. The legislator of the Federal Constitution of 1988, in the caput of art. 225, as listed the duty of the Public Power and of the community defending and preserving the environment ecologically balanced for the present and future generations. There are prescribed in the Law of the Waters (Law n.º 9.433, of January 08, 1997) several criteria that must be obeyed in the appropriation of the hydric resources in Brazil. Environmental important beginnings as the equitable access to the water, the sustainable development, among others, are informers of the national legislation, but are not sufficient to avoid depletion of water sources. Water as well to diffuse public ownership and ownership should be managed in a democratic and participatory form by means of the use of instruments that can equate conflicts and avoid the degradation of the resource. After being held a preliminary analysis of legal concepts and proposals related to water resources and hydroelectric reservoirs, will be addressed in the present work, the historical and socio-environmental reservoir of the Balbina Hydroelectric Scheme in the State of Amazonas, so that to the end some conflicts are described in the location and the instruments of management that can contribute to the reduction of these conflicts. The present dissertation holds like technique of collection of informations the bibliographical inquiry and through the analytical descriptive method a critical and propositive reflection intends in the present inquiry to carry out about the referent questions to the hydric constant resources in the reservoirs of the hydroelectric stations, in special in that what they form the reservoir of the Hydroelectric station of Balbina. Keywords: Hydric resources. Socioenviromental Conflicts. Sustainable development. Hydroelectric power plant of Balbina.